Comparative analysis of interference protection of "Friend-Foe" radar identification systems - Svyd, I.V.; Tkach, M.G.; Obod, I.I. (Radiotekhnika, 2022)
The paper examines the existing systems of radar identification based on the "friend-foe" feature from the point of view of immunity evaluation. Currently, there are two systems of the radar identification based on the characteristic of "friend-foe", namely, the "Password" and MkXIIA. They are the radar identification systems based on the "home-foreign" feature. The former of the specified systems operates in a frequency range that differs from the frequency range of secondary radar systems, while the second one operates in the frequency range of secondary radar. These systems are ones of the main information resources of the airspace control system and are built on the principles of a one-channel or two-channel information transmission system. It allows the interested party, both an unauthorized use of this information resource for remote determination of the coordinates of aerial objects, on the one hand, and twisting the information of these information resources, on the other hand, which leads to unpredictable results. The purpose of the work is to assess the immunity of existing radar identification systems based on the "friend-foe" feature. The analysis of the interference protection of existing systems for the object radar identification based on the "friend-foe" feature, built on the principles of interrogative and non-interrogative information systems presented in this work, showed that the use of rectangular radio signals with time-pulse modulation as request and response signals emitting by air objects, has low immunity and excludes the energy stealthiest of the respondents of aerial objects. And, as a result, it allows for unauthorized calculation of the coordinates of air objects by the interested party based on the emitted identification signals on the basis of "friend-foe".